A decision aid for additional findings in genomic sequencing: Development and pilot testing. Issue 5 (May 2021) - Freed, Amanda S.; Gruß, Inga; McMullen, Carmit K.; Leo, Michael C.; Kauffman, Tia L.; Porter, Kathryn M.; Muessig, Kristin R.; Eubanks, Donna; Goddard, Katrina A.B.; Wilfond, Benjamin S.; Liles, Elizabeth G.
Highlights: Decision aids have been used in many fields to support quality decision making. Additional findings are optional for individuals undergoing genomic sequencing. We designed a novel decision aid about medically actionable additional findings. It is targeted for a diverse cohort of adults including adults with low literacy. The decision aid may help users to make an informed, values-based choice. Abstract: Objective: To describe the development of a web-based, patient-facing decision aid to support patients and research participants to make an informed, values-based decision about whether to receive additional results from genomic sequencing. Methods: We developed the decision aid following the multi-step process described in the International Patient Decision Aids Standards. This utilized literature review, focus groups, and alpha testing with research participants undergoing clinical genomic sequencing. Results: The decision aid, the Optional Results Choice Aid (ORCA), includes a seven-question "values clarification exercise, " illustrative patient quotes, and summative guidance for the user. The decision aid was found to be highly readable, acceptable and relevant in alpha testing. Conclusion: We developed a decision aid to support informed, values-based decision making for patients and research participants considering whether to receive additional results from genomic sequencing. ORCA is being implemented in the NHGRI-funded Cancer Health Assessment Reaching Many (CHARM) study, where we are measuring informed values-choice congruence. Practice implications: ORCA was designed to support patients and research participants to make an informed, values-based decision about whether to receive additional results from genomic sequencing.